Neurocognitive impairment in Ugandan children with sickle cell anemia compared to sibling controls: a cross-sectional study - Bangirana, Paul; Boehme, Amelia K.; Birabwa, Annet; Opoka, Robert O.; Munube, Deogratias; Mupere, Ezekiel; Kasirye, Phillip; Muwanguzi, Grace; Musiimenta, Maxencia; Ru, George; Green, Nancy S.; Idro, Richard (Frontiers in Stroke, 2024)
Introduction The neurocognitive functions in Ugandan children aged 1–12 years with sickle cell anemia (SCA) were compared to their non-SCA siblings to identify risk factors for disease-associated impairment. Methods This cross-sectional study of the neurocognitive functions in children with SCA (N = 242) and non-SCA siblings (N = 127) used age- and linguistically appropriate standardized tests of cognition, executive function, and attention for children ages 1–4 and 5–12. Test scores were converted to locally derived age-normalized z-scores. The SCA group underwent a standardized stroke examination for prior stroke and transcranial Doppler ultrasound to determine stroke risk by arterial flow velocity. Results The SCA group was younger than their siblings (mean ages 5.46 ± 3.0 vs. 7.11 ± 3.51 years, respectively; p < 0.001), with a lower hemoglobin concentration (7.32 ± 1.02 vs. 12.06 ± 1.42, p < 0.001). The overall cognitive SCA z-scores were lower, −0.73 ± 0.98, vs. siblings, −0.25 ± 1.12 (p < 0.001), with comparable findings for executive function of −1.09 ± 0.94 vs. −0.84 ± 1.26 (p = 0.045), respectively. The attention z-scores for ages 5–12 for the SCA group and control group were similar: −0.37 ± 1.4 vs. −0.11 ± 0.17 (p = 0.09). The overall differences in SCA status were largely driven by the older age group, as the z-scores in the younger subsample did not differ from controls. Analyses revealed the strongest predictors of poor neurocognitive outcomes among the SCA sample to be the disease, age, and prior stroke (each p < 0.001). The impacts of anemia and SCA were indistinguishable. Discussion Neurocognitive testing in children with SCA compared to non-SCA siblings revealed poorer SCA-associated functioning in children older than age 4. The results indicate the need for trials assessing the impact of disease modification on children with SCA.